Theory-practice gap: The knowledge and perception of Nigerian nurses - Kabir Ozigi Abdullahi; Shahrzad Ghiyasvandian; Marzieh Hasanpour (Wolters Kluwer Medknow Publications, 2022)
Background: The theory-practice gap can be described as a lack of ability to relate the knowledge acquired in academics and research work with practice. This study aims to assess the knowledge and the perception of Nigerian nurses on the theory-practice gap in Nursing. Materials and Methods: This cross-sectional correlational study was carried out with a sample of 196 nurses who were working in the Federal Medical Centre Keffi and Aminu Kano Teaching hospital in Kano, all from the northern part of Nigeria, from April to June 2019. The participants were selected using a convenient sampling technique, where a self-administered questionnaire was utilized to collect the data and analysis was undertaken using SPSS. Results: The results of this study showed that 83.80% of respondents had good knowledge and 89.10% of the respondents had good perceptions. The levels of knowledge were significantly different in correlation with the educational level of respondents (χ2 = 13.88, df = 6, p = 0.022), which was determined using a Fischer exact test. Also, the level of perception was significantly different when considering the nature of work participants undertook (X2 = 7.65, df = 2, p = 0.022). Conclusions: Given the participants' awareness and perceptions in this study, it is clear that they are well informed of the theory-practice gap. This is a call for all professionals at an individual and organizational level to work, as it will translate into gap minimization, thereby increasing the quality of health care delivery as nurses constitute the largest part of the health care team in Nigeria.